2017
DOI: 10.1103/physrevlett.118.036804
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Entanglement Witness from Electrical Current Correlations

Abstract: Despite great efforts, an unambiguous demonstration of entanglement of mobile electrons in solid state conductors is still lacking. Investigating theoretically a generic entangler-detector setup, we here show that a witness of entanglement between two flying electron qubits can be constructed from only two current cross correlation measurements, for any nonzero detector efficiencies and non-collinear polarization vectors. We find that all entangled pure states, but not all mixed ones, can be detected with only… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 64 publications
1
23
0
Order By: Relevance
“…Alternatively, ferromagnetic leads may be used to determine the spin state of the electrons 41 , 42 . Thus, by combining the fast charge detection with the spin readout, one may witness and certify the quantum entanglement of the split Cooper pairs 43 , 44 . Ultimately, several Cooper pair splitters may be combined to realize the first rudimentary quantum information algorithms using split Cooper pairs.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, ferromagnetic leads may be used to determine the spin state of the electrons 41 , 42 . Thus, by combining the fast charge detection with the spin readout, one may witness and certify the quantum entanglement of the split Cooper pairs 43 , 44 . Ultimately, several Cooper pair splitters may be combined to realize the first rudimentary quantum information algorithms using split Cooper pairs.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, several ways were proposed to test the performance of a Cooper pair splitter device, starting from current or noise correlations, [19][20][21] through spin selective measurements [22][23][24][25] to proving the entanglement by demonstrating the violation of the Bellinequality 18,[26][27][28][29][30][31][32] or using more complex spin-qubit or circuit quantum electrodynamics architectures 17,33,34 or even time domain measurements. 35 The experiments primarily focused on spatial current correlations.…”
Section: Introductionmentioning
confidence: 99%
“…1. To certify the entanglement of the split Cooper pairs, it has been suggested that Bell inequalities can be formulated for the cross correlations of the output currents, using ferromagnetic leads as spin filters [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%